La lógica perversa y las exigencias académicas : Una aproximación a las perspectivas de los profesores en Educación Física de la Universidad Nacional de La Plata (UNLP) sobre el Programa de Incentivos a los Docentes-Investigadores - Levoratti, Alejo (2013)
The proposal of this article is to analyze the perspectives of the teachers of Physical Education of the UNLP as regards the Programa de Incentivos (PI). On one hand, it analyses the Programa de Incentivos as a State policy directed to all National Universities, attending to its capacity in setting and determine actions. On the other hand, this article looks into understanding the dynamics characteristics of the actors/agents. This study tries to show the perspectives and tensions generated by the PI, since at the same time it made possible the emergence of a new social actor, the teacher- researcher, as well as it generated many difficulties in its incorporation and development.